Terror at Sea - Masters, Anthony (Franklin watts, 2000)
Jacques and Frederic thought they might be able to escapes- that is, unless one of them got wounded. At the first sign of blood the sharks would attack them both...
Keywords: Juvenile Fiction / Adventure